2008
DOI: 10.1254/jphs.fp0070911
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Organic Anion Transporters and Organic Cation Transporters With Mycotoxins

Abstract: Abstract. Mycotoxins are secondary metabolites of moulds that which exert adverse effects in humans and animals. It is known that direct cellular toxicity is often associated with increased cellular accumulation of toxic compounds, and membrane transport may be the first fundamental stage in the development of the cytotoxicity. To elucidate the entry pathway for mycotoxins into cells, we have investigated the interactions of human and rat organic anion transporters (hOATs/ rOats) and human organic cation trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 32 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…[ Other materials used in this study were the same as those previously reported (11). AAs were subjected to preparative high-performance liquid chromatography (HPLC) to obtain AA-I (22 mg) and AA-II (19 mg) and were identified by comparing 1 H-nuclear magnetic resonance spectroscopy and mass spectrometry spectral data with reported data (12).…”
Section: Interactions Of Human Organic Anion Transporters With Aristomentioning
confidence: 99%
See 1 more Smart Citation
“…[ Other materials used in this study were the same as those previously reported (11). AAs were subjected to preparative high-performance liquid chromatography (HPLC) to obtain AA-I (22 mg) and AA-II (19 mg) and were identified by comparing 1 H-nuclear magnetic resonance spectroscopy and mass spectrometry spectral data with reported data (12).…”
Section: Interactions Of Human Organic Anion Transporters With Aristomentioning
confidence: 99%
“…Uptake experiments using S2 hOATs (S2 hOAT1, S2 hOAT2, S2 hOAT3, and S2 hOAT4) were performed as previously described (11). For kinetic analysis, S2 hOAT1 and S2 hOAT3 were incubated at 37˚C in a solution containing either [ 14 C]PAH (hOAT1) or [ 3 H]ES (hOAT3) at different concentrations in the absence or presence of AA-I for 2 min.…”
Section: Interactions Of Human Organic Anion Transporters With Aristomentioning
confidence: 99%
“…Interactions of FB1 with organic anion transporter of rat (rOAT1) 45) and of human (hOAT3) 46) were reported in the inhibition study using typical substrates. These data suggest the possibility of efficient uptake in liver and reuptake in kidney of FB1 through OAT family of transporters.…”
Section: Metabolism and Transportmentioning
confidence: 99%
“…Finally, environmental chemicals, such as diesel exhaust particle extract and pesticides, have been demonstrated to interact with drug transporters through competitive mechanisms or to modify their expression (Table ) . Data are still sparse, and additional in vitro and in vivo studies are required to quantify pollutant‐transporter interplays.…”
Section: Environmental Factors Associated With Altered Drug Transportmentioning
confidence: 99%